Teori-Teori Belajar dan Kaitannya Dengan Pengembangan Kurikulum PAI - Hayati, Mufidah; Murdiana, Murdiana; Arifmiboy, Arifmiboy (Institut Teknologi Pendidikan Indonesia, 2023)
Signs of learning people can be seen and the occurrence of transformations within a person Transformation is a change in behavior Changes in behavior touch 3 educational domains within the learner, namely cognitive abilities, affective domains, and psychomotor domains or better known as knowledge domains, attitude domains, and domain of skills So and that requires situations and conditions of teaching and learning activities that support, available facilities, and so on must be adjusted to the educational goals to be achieved This study aims to find out the learning theory that must be known by teachers and students so that learning objectives can be achieved effectively and efficient This research is